Study of the antibacterial activity of new modified galenic and novogalenic phytosubstances from Vaccinium vitis-idaea leaves - Tsemenko, K V; Kyreev, I V; Osolodchenko, T P (Annals of Mechnikov's Institute, 2020)
The purpose of the work is to study the antibacterial activity of new modified galenic and novogalenic phytosubstances from Vaccinium vitis-idaea leaves. Materials and methods. The object of our research new modified galenic and novogalenic phytosubstances from Vaccinium vitis-idaea leaves. Pharmacopoeia agar diffusion method biological method for determining the activity of antibiotics, based on the ability of molecules antibiotic substances diffuse in agar media and form zones of inhibition, in which the test microorganisms used do not develop sensitive to the antibiotic under study. The study of antibacterial activity of the phytosubstances was in the laboratory of biochemistry of microorganisms and nutrient medium of the Mechnikov Institute of Microbiology and Immunology under the direction of сandidate of biological sciences Osolodchenko T.P. The reference drug was Inurek, recommended by the European Association of Urology for the prophylactic treatment of urinary tract infections. Results. We have identified the most active phytosubstance, which is the glycosides of phenolic compounds in combination with the arginine, dissolved in 50% alcohol. It has been established that polysaccharides from the leaves of Vaccinium vitis-idaea leaves may have a low antibacterial effect, and in the complex with phenolics, they do not infuse an antibacterial effect on the antibacterial effect. It has been established that phenolics from half of the leaves of lingonberry extraordinarily exhibit a greater antibacterial effect in the presence of glucosides. Conclusions. A screening study of the antibacterial activity of 13 new modified galenic and novogalenic phyto-substances from Vaccinium vitis-idaea leaves carried out. The most active was phytosubstance 12, which is a complex of glycosides of phenolic compounds with arginine. It has been proven that it is phenolic compounds in the form of glycosides that have a more pronounced effect in the main relations of uropathogens than their aglycones. DOI: 10.5281/zenodo.4038913